Race, Place, and Memory : Deep Currents in Wilmington, North Carolina - Mulrooney, Margaret M., 1966- (Book collections on Project MUSE., 2018)
This book uses the 1998 commemoration of the Wilmington Race Riot of 1898 as a springboard to explore the historic roots of modern disagreements over cultural heritage.